THE CONDITION OF THE GASTRIC MUCOSA IN CHILDREN WITH NEPHROTIC SYNDROME - Bobomuratov Turdiqul Akramovich; Samadov Abduqakhkhor Abdurakhmonovich (Modern American Journals, 2025)
In this article, 126 children with nephrotic syndrome and with changes in the gastrointestinal tract were classified into 3 groups based on clinical laboratory forms of nephrotic syndrome. 1- Control group steroid-sensitive nephrotic syndrome 34 (26.98%) and Major 2- group frequent nephrotic syndrome-54 (42.86%), 3-group steroid-dependent nephrotic syndrome -38 (30.16%). Changes in the gastric mucosa of sick children were estimated based on the results of gastro duodenoscopy and method of enzyme immunoassay pepsinogen I, pepsinogen II and the ratio of pepsinogens I/II in blood serum. Changes in the gastric mucosa have been found to correlate with clinical forms of the disease the duration of treatment with glucocorticosteroids.
Keywords: Children, nephrotic syndrome, stomach, mucous membrane, gastro duodenoscopy, pepsinogen.